Profesionalisme Pendidik Bahasa Arab dalam Perspektif Filsafat Etika: Implikasinya terhadap Pengembangan Kopetensi Guru - ABDUL WARIS; Kamal Yusuf (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyse the professionalism of Arabic language educators through the perspective of ethical philosophy and its implications for teacher competency development. The approach used is library research with a qualitative-descriptive method, through theoretical studies and critical analysis of literature related to professionalism, deontological ethics, and Arabic language education. The results of the study show that the professionalism of Arabic language teachers does not only depend on mastery of technical competencies—such as pedagogy, linguistics, and learning methodology—but also on the internalisation of ethical values such as honesty, responsibility, fairness, and cultural sensitivity. Within the framework of deontological ethics, teachers are positioned as moral agents who have an obligation to educate with integrity and social responsibility. The main challenges identified include the incompatibility of teachers' academic backgrounds, the lack of integration of professional ethics in the teacher training curriculum, and bureaucratic pressure oriented towards quantitative results. The implications of this study emphasise the importance of integrating a professional ethics curriculum, moral reflection-based training, and the establishment of a code of ethics and ethical supervision mechanisms as strategies for developing the competence of professional and ethical Arabic language teachers. Thus, the development of teacher professionalism must be directed holistically, covering technical, moral, and spiritual aspects so that Arabic language learning can take place in a meaningful and transformative manner. Keywords: teacher professionalism, Arabic language, ethical philosophy, teacher competence.